About the impact of individually tailored plyometric training on the competitive performance of amateur boxers - Anvar, A.-S. M. A.; Myasnikova, T. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the impact of individualised physical training using plyometric exercises on the competitive performance of amateur boxers.